PERAN STAKEHOLDER DALAM MENGOPTIMALKAN PEMANFAATAN APLIKASI JAKI UNTUK MEWUJUDKAN SMART GOVERNANCE - Salsabila, Srinata; ., Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Smart City is a concept to maximize the use of technology in the order of a city. Smart governance is one of the indicators of the creation of a Smart City. One of the efforts to realize this is by creating the JAKI application. The JAKI application is the result of government cooperation with stakeholders, namely the community, government and the private sector. Optimal utilization is one of the important indicators that influence the realization of smart governance in Jakarta. Therefore, the purpose of this study is to find out who are the stakeholders involved in optimizing the use of the JAKI application and to find out and analyze how the role of stakeholders in optimizing the use of the JAKI application to realize smart governance in Jakarta. This research uses descriptive qualitative methods with data collection techniques, namely interviews and observations. The results showed that the utilization of the JAKI application was still not optimal because there were still many people who did not know the function of the JAKI application, few stakeholders who were directly involved and the role of stakeholders who were not good at optimizing the use of the application.